Amino Acids Composition of Non-Structural Protein in SARS-CoV-2 the Cause of COVID-19 Pandemic - Suprianto Suprianto; Ni Kadek Dewi Permatasari; Gusti Ayu Kadek Yunita Safitri (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2021)
The transmission of COVID-19 is one of the global problems that has caused many deaths. This pandemic was caused by SARS-CoV-2, which has several non-structural proteins (nsp1-nsp16). The non-structural proteins in SARS-CoV-2 have different amino acid compositions. The purpose of this study was to analyze the amino acid composition of SARS-CoV-2. This study used computational methods in silico analysis to analyze the amino acid composition of the target protein. The target protein sequence database was obtained from the NCBI website with the identity number NC_045512.2. Non-structural protein with the shortest amino acid length is owned by nsp7 (83 aa) with a molecular weight of 9239.34 Daltons, nsp9 (113 aa) with a molecular weight of 12377.54, and nsp1 (180 aa) with a molecular weight of 19774.35, while non-structural proteins with amino acid composition the longest is found in nsp3 (1945 aa) with a molecular weight of 217241.50 Daltons, nsp12 (932 aa) with a molecular weight of 106654.88 Daltons and nsp2 (638 aa) with a molecular weight of 70507.81 Daltons. The amino acid composition of each target protein varies in length, weight, and frequency. Information obtained from this reasearch result can be used as the basis for studying the characteristics of the non-structural protein in SARS-CoV-2, which causes the COVID-19 pandemic based on the composition of the constituent amino acids.